Field Trip Report – Long Puah’s Kindergarten Solar System Installation & Long Lamai’s Telecentre Solar System Troubleshooting - Jumat, Yusri (Isiti-coERI, 2015)
Our purpose in Long Puah was to migrate one of the existing Solar System Unit from the long house to a newly built kindergarten building next to the long house. Mr Simon Tsai (the previous lighting project contractor) had kindly donated one unit of the solar system Due to the donation, the objective was changed instead of migrating one existing solar system at the long house to a kindergarten, to install a new solar system at the kindergarten.